2014
DOI: 10.1128/jvi.00454-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Amino Acid Substitutions with Compensational Effects in the Attachment Protein of Canine Distemper Virus

Abstract: The hemagglutinin (H) gene of canine distemper virus (CDV) encodes the receptor-binding protein. This protein, together with the fusion (F) protein, is pivotal for infectivity since it contributes to the fusion of the viral envelope with the host cell membrane. Of the two receptors currently known for CDV (nectin-4 and the signaling lymphocyte activation molecule [SLAM]), SLAM is considered the most relevant for host susceptibility. To investigate how evolution might have impacted the host-CDV interaction, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Some South African isolates have an M195I substitution (49) located close to the T192A mutation in our SLAMrev virus. A different substitution at this position (M195V) may influence receptor binding (39). Many isolates of the Asia-I lineage have a Y549H substitution (50), which is immediately adjacent to residues 547/548 mutated in the SLAM-blind virus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some South African isolates have an M195I substitution (49) located close to the T192A mutation in our SLAMrev virus. A different substitution at this position (M195V) may influence receptor binding (39). Many isolates of the Asia-I lineage have a Y549H substitution (50), which is immediately adjacent to residues 547/548 mutated in the SLAM-blind virus.…”
Section: Discussionmentioning
confidence: 99%
“…The two phases of CDV infection and disease, colonization of immune tissues and spread to epithelia, are determined by interaction with the two receptors SLAM and nectin-4, respectively (37,38). Evolutionary forces drive H protein variability during virus circulation, and compensatory mutations often arise at other positions that offset detrimental changes in the protein (39). By infecting susceptible animals with viruses that are no longer able to interact with either SLAM or nectin-4 (26, 27), we can gain insight into the compensatory mechanisms that affect the interactions between CDV and its receptors.…”
mentioning
confidence: 99%
“…Recent studies showed that similar amino acid changes could affect virulence and infectivity of different Canine distemper virus (family Paramyxoviridae , genus Morbillivirus ) strains, but such changes are often neutralized by compensatory mutations that preserve the biologic activity of H protein ( 15 ). Furthermore, despite the high sequence homology observed between N, P, and H genes of the DMV strain identified in the newborn fin whale in our study and in the isolates recovered from DMV-affected cetaceans during the 1990–1992 and the 2006–2007 epidemics (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%
“…Although the single amino acid substitution, p.Ala451Thr, did not cause substantial variations in the structure of H antigen, the effect of the variation on protein functions is unclear. Recent studies showed that similar amino acid changes could affect virulence and infectivity of different Canine distemper virus (family Paramyxoviridae , genus Morbillivirus ) strains, but such changes are often neutralized by compensatory mutations that preserve the biologic activity of H protein ( 15 ). Furthermore, despite the high sequence homology observed between N, P, and H genes of the DMV strain identified in the newborn fin whale in our study and in the isolates recovered from DMV-affected cetaceans during the 1990–1992 and the 2006–2007 epidemics (GenBank accession no.…”
Section: Discussionmentioning
confidence: 99%